ROLE OF 5-HT7 RECEPTORS ON LORDOSIS BEHAVIOUR AND LH RELEASE IN THE FEMALE RATS - Siddiqui, Arif; Shaharyar, Saeeda (Pakistan Journal of Physiology, 2006)
Background: The present study was designed to inves tigate the role of the 5-HT7 receptors in lordosis and release of LH and compare the lordotic responses with 5-HT1A agent. Methods: Ovariectomised but oestradiol benzoate (OB) (10 ug) for 48 h plus by progesterone (0.5 mg)- primed receptive rats were used for the study. Thirty min. prior to progesterone,. 5-HT 1A and 5- HT7 agonists were administered intra-peritoneally (i.p.). Lordotic quotient and release of LH were measured. Agonistic effect was then antagonized by respective antagonists. Effects on the above parameters were noted and correlated for possible interplay. Results: 5-HT7 agonist mimicked inhibitory effect of 8-OH DPAT on lordosis in receptive rats, however, the response was generally attenuated. Treatment by 5-HT1A antagonist, WAY 100135 causing a protective effect was evident transiently. Attenuation of lordotic quotient was again evident in rats treated with 5-HT7 antagonist. 5-HT and the 5-HT1A/7 receptor agonist, 8-OH-DPAT, injected i.p. into the female rat inhibit the LH release and the effects of both are blocked by 5-HT1A antagonist, WAY 100135 and 5-HT7 antagonist, SB 269970-A as both 5-HT1A agonist, 8-OH-DPAT and 5-HT7 agonist, 5-CT have moderate activity at the 5-HT7 receptor subtype, indicating the possibility that this subtype might mediate these effects has been investigated. Ovariectomised but steroids primed rats induces an LH surge. (5-CT), a potent but non-selective agonist at 5-HT7 receptors, like 5-HT and 8-OH-DPAT inhibited the LH surge at 2 mg injected i.p.